2017
DOI: 10.3390/socsci6020055
|View full text |Cite
|
Sign up to set email alerts
|

Science Possible Selves and the Desire to be a Scientist: Mindsets, Gender Bias, and Confidence during Early Adolescence

Abstract: In the United States, gender gaps in science interest widen during the middle school years. Recent research on adults shows that gender gaps in some academic fields are associated with mindsets about ability and gender-science biases. In a sample of 529 students in a U.S. middle school, we assess how explicit boy-science bias, science confidence, science possible self (belief in being able to become a scientist), and desire to be a scientist vary by gender. Guided by theories and prior research, we use a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 82 publications
3
20
0
Order By: Relevance
“…There are multiple and complex reasons that students may have domain-specific growth mindsets (Matheson, 2015;Stipek & Gralinski, 1996), including the influence of cultural norms, expectations and stereotypes. For example, those who are underrepresented within science, mathematics or engineering by gender may receive gender-essentialist fixed mindset messages such as boys are good at science (Wonch Hill et al, 2017) or girls are not good at math (Tomasetto, Alparone, & Cadinu, 2011).…”
Section: Growth and Fixed Mindsetmentioning
confidence: 99%
“…There are multiple and complex reasons that students may have domain-specific growth mindsets (Matheson, 2015;Stipek & Gralinski, 1996), including the influence of cultural norms, expectations and stereotypes. For example, those who are underrepresented within science, mathematics or engineering by gender may receive gender-essentialist fixed mindset messages such as boys are good at science (Wonch Hill et al, 2017) or girls are not good at math (Tomasetto, Alparone, & Cadinu, 2011).…”
Section: Growth and Fixed Mindsetmentioning
confidence: 99%
“…Although solving our society and our planet's most pressing challenges requires an innovative STEM workforce, many youth (especially girls) lose interest in STEM around middle school (reviewed in ref. ). Quality, widespread, accessible informal STEM learning experiences (i.e., science communication), however, are known to be effective at improving K‐12 student's science literacy, helping to develop positive science identities, and ultimately increasing STEM persistence .…”
Section: Engaging With Youthsmentioning
confidence: 97%
“…In the United States there is a gender conundrum in science: girls have higher science grades but are less likely to pursue degrees and careers in science (Buday et al, 2012;Else-Quest et al, 2013;Riegle-Crumb et al, 2006). Many factors may explain why girls may be less likely to persist in science including differences in science confidence, lack of female role models, or lack of parental or peer support, all which may impact whether girls see themselves as science people or not (Archer et al, 2013;Correll, 2004;Gauthier et al, 2017;Hill et al, 2017;Riegle-Crumb et al, 2006). Additionally, Lareau (2011) found that there were marked differences between boys and girls with respect to the types of after-school activities that they participated in, although the study did not focus on science-specific activities or on differences in geographic location.…”
Section: Socioeconomic Status Gender and Ethnicity: Informalmentioning
confidence: 99%
“…One early outcome of research on youth STEM persistence is that recognition that a strong science identity is an indicator of a greater likelihood that youth will persist in science through high school, college and beyond. (Hill et al, 2017;Stets et al, 2017). Potential for adolescents to engage with science activities during out-of-school times is an important element for developing and maintaining a science identity (After-school Alliance, 2013).…”
Section: Introductionmentioning
confidence: 99%